2006
DOI: 10.1385/endo:30:2:213
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Neonatal Exposure to Nicotine Disrupts Ovarian Function and Fertility in Adult Female Rats

Abstract: Women born to mothers who smoked during pregnancy have been shown to have impaired fertility, although the mechanisms underlying this association are unknown. Nicotine administration in adult animals has adverse effects on the ovary and uterus; however, the effects of fetal exposure to nicotine on postnatal ovarian function have not been determined. The goal of this study was to assess the effect of fetal and neonatal exposure to nicotine on ovarian function and fertility of the offspring. Nulliparous female W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 40 publications
7
52
0
1
Order By: Relevance
“…With this dose of nicotine, the concentration of active nicotine (nicotine free base concentration) is consistent with daily nicotine exposure in a typical smoker (22). The maternal steady state serum cotinine (major metabolite of nicotine) levels resulting from this exposure is 135.9 ± 7.86 ng/ml (23) and is within the range of cotinine concentrations reported in pregnant smokers during both early pregnancy and late pregnancy (24). At postnatal day 1 (PND1) litters were culled to eight to assure uniformity of litter size between treated and control litters.…”
Section: Maintenance and Treatment Of Animalsmentioning
confidence: 52%
“…With this dose of nicotine, the concentration of active nicotine (nicotine free base concentration) is consistent with daily nicotine exposure in a typical smoker (22). The maternal steady state serum cotinine (major metabolite of nicotine) levels resulting from this exposure is 135.9 ± 7.86 ng/ml (23) and is within the range of cotinine concentrations reported in pregnant smokers during both early pregnancy and late pregnancy (24). At postnatal day 1 (PND1) litters were culled to eight to assure uniformity of litter size between treated and control litters.…”
Section: Maintenance and Treatment Of Animalsmentioning
confidence: 52%
“…The dose of nicotine used in this study (1 mg/kg per day nicotine bitartrate) results in maternal serum cotinine concentrations of 136 ng/ml (Holloway et al 2006), which is within the range of cotinine levels (80-163 ng/ml) reported in women who are considered as 'moderate smokers' (Eskenazi & Bergmann 1995). In addition, this dose of nicotine resulted in serum cotinine concentrations of 26 ng/ml in the nicotineexposed offspring at birth (Holloway et al 2006), which is also within the range (5-30 ng/ml) observed in infants nursed by smoking mothers (Luck & Nau 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The dose of nicotine used in this study (1 mg/kg per day nicotine bitartrate) results in maternal serum cotinine concentrations of 136 ng/ml (Holloway et al 2006), which is within the range of cotinine levels (80-163 ng/ml) reported in women who are considered as 'moderate smokers' (Eskenazi & Bergmann 1995). In addition, this dose of nicotine resulted in serum cotinine concentrations of 26 ng/ml in the nicotineexposed offspring at birth (Holloway et al 2006), which is also within the range (5-30 ng/ml) observed in infants nursed by smoking mothers (Luck & Nau 1985). Although 15-20% of pregnant women smoke (Andres & Day 2000, Okuyemi et al 2000, many women attempt to stop smoking during pregnancy and then relapse following parturition (McBride & Pirie 1990, Castrucci et al 2006, Thyrian et al 2006, resulting in nicotine exposure at conception and during lactation only.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no human studies examining the reproductive outcomes in children exposed to NRTs in utero. Studies in animal models have identified that prenatal exposure to nicotine alone can result in increased germ cell depletion and altered steroidogenesis in male offspring (Lagunov et al 2011, Paccola et al 2014) and increased ovarian cell apoptosis, altered steroidogenesis, and impaired fertility in female offspring (Holloway et al 2006, Petrik et al 2009.…”
Section: Postnatal Health Outcomesmentioning
confidence: 99%
“…Importantly, these cytokines play key roles in germ cell survival and gonadal steroidogenesis (Bornstein et al 2004, Perez et al 2013, Field et al 2014. As fetal exposure to nicotine in rodents has been demonstrated to cause germ cell loss and altered steroidogenesis (Holloway et al 2006, Petrik et al 2009, Lagunov et al 2011, Paccola et al 2014, it is biologically plausible that these effects may be mediated by an altered inflammatory response, although this has yet to be experimentally determined.…”
Section: The Role Of Inflammationmentioning
confidence: 99%